Sensory Integration and Functional Reaching in Children With Rett Syndrome/Rett-Related Disorders. (August 2019) - Drobnyk, Wendy; Rocco, Karen; Davidson, Sara; Bruce, Susan; Zhang, Fang; Soumerai, Stephen B
Background: The loss of functional hand skills is a primary characteristic of Rett syndrome. Stereotypies, dyspraxia, and other sensory processing issues severely limit the individual's ability to reach toward and sustain grasp on objects. This loss of functional reach and grasp severely limits their ability to participate in self-help, play, and school-related activities. We proposed that Ayres Sensory Integration (ASI) treatment would improve sensory processing and motor planning, which would lay the sensory-motor groundwork for improving grasp of objects, an important first step in developing functional hand use. Objective: We examined effects of ASI treatment on rate of reaching and grasping for children with Rett syndrome/Rett-related disorders. Methods: We used an interrupted time series design to measure changes in outcome variables occurring after intervention initiation and cessation. We analyzed daily video observations during baseline, intervention, and post-intervention periods, over a span of 7 months. Results: During baseline, rate of grasping declined moderately. There was a 15% increase in grasping from the end of baseline to end of the post-intervention period. There was no significant change in rate of reaching. Conclusions: This study provides preliminary data showing very small improvements in hand grasp of children with Rett syndrome following ASI treatment; larger studies in diverse settings are needed to establish the effectiveness of this approach. This study shows that an interrupted time series research design provides a valid template for evaluating interventions for children with rare disorders.